Health risk perception by exposure to pollutant mixtures: the case of agricultural valleys in Mexicali and San Quintín, Baja California, Mexico - Evarista Arellano; Lourdes Camarena; Christine von Glascoe; Walter Daesslé (Universidad de Antioquia, 2009)
Objective: To examine risk perception based on principles of intuitive toxicology and characteristics of exposure to mixtures of contaminants in residents of two sites in Baja California, Mexico: the Colorado River estuary at the intersection of Hardy and Colorado rivers and San Quintin Valley. Methodology: A questionnaire was applied to 166 participants and it was analyzed four criteria of exposure to contaminants: types, grades, levels and intensity. Through intuitive toxicology, three elements of perception risk were classified: occupational exposure, environmental exposures and health effects. It was applied a cluster analysis (c a) for exploratory classification and principal component analysis (p c a) to explain the relationships between variables. Results and discussion: vulnerable participants to health effects from exposure to mixtures of pollutants and understanding of risk are related to exposure characteristics, as only they perceive acute complaints and they exclude chronic degenerative, which is explained by the concept of intuitive toxicology. The perception of risk is measured by schooling and wage income, agricultural workers do not detect effects of such chronic health from exposure to mixtures of pollutants